Hematological and blood chemistry profiles of the Mediterranean pond turtle (Mauremys leprosa) in a Portuguese wildlife rehabilitation center - Gonçalo N. Marques; Joana S. Guerra; Miriam O. Leal; Miriam O. Leal; Miriam O. Leal; João Neves (Frontiers in Veterinary Science)
The Mediterranean pond turtle (Mauremys leprosa) is increasingly recognized as a sentinel species for freshwater ecosystem health due to its resilience to environmental pollutants. Despite its ecological significance, there is a lack of research on the blood profile of this vulnerable species. This study assessed the hematological and biochemical profile of healthy individuals admitted to Zoomarine’s Porto d’Abrigo rehabilitation center in southern Portugal between 2015 and 2024. This investigation revealed significant differences between the established data and the reference intervals reported in a Spanish study, notably in total erythrocyte (RBC) counts, packed cell volume (PCV), differential counts of lymphocytes and eosinophils, total protein (TP), creatine kinase (CK), potassium (K+), phosphorous (PHOS), and glucose (GLU) levels. Significant differences were also observed between captive and wild-rescued individuals in monocyte percentages, aspartate aminotransferase (AST), and CK levels. No seasonal influence was detected except in the differential count of eosinophils. These findings indicate a possible geographical, environmental, and captivity-induced variation, providing the first comprehensive species-specific hematological and biochemical intervals for M. leprosa derived from a healthy population. This study enhances the understanding of M. leprosa health within a One Health framework by offering critical diagnostic benchmarks for veterinary care and facilitating conservation strategies.